Unit one - Water resources and scarcity. [Training/Course material] - Fraiture, Charlotte de; Manning-Thomas, Nadia; David, S. (2009)
This module is about water resources management. It is therefore necessary to understand what water resources are. This unit provides a general introduction to the terms and concepts that help us to understand water resources and their various forms and movements through our systems. What is the hydrological cycle and what does this mean for availability, use and management of water? This section provides an introduction to all aspects of input, storage, changes in state, use and output of water through our land, water and atmosphere systems, with special attention paid to the inclusion of groundwater as a water resource. This important background information on water resources is vital for being able to address the management aspect of the module's title.